How do public perceptions affect the security of connected places? A systematic literature review - Dutkowska-Zuk, A; Bourne, J; An, C; Gao, X; Cetinkaya, O; Novitzky, P; Ogunniye, G; Cooper, R; De Roure, D; McCann, J; Watson, J; Watson, T; et al. (MDPI, 2024)
This systematic literature review explores the scholarly debate around public perceptions and behaviors in the context of cybersecurity in connected places. It reveals that, while many articles highlight the importance of public perceptions and behaviors during a cyberattack, there is no unified consensus on how to influence them in order to minimize the attack’s impact and expedite recovery. Public perceptions can affect the success and sustainability of connected places; however, exactly how and to what extent remains unknown. We argue that more research is needed on the mechanisms to assess the influence of public perceptions and associated behaviors on threats to security in connected places. Furthermore, there is a need to investigate the models and tools currently being deployed by connected place design and management to understand and influence public perceptions and behaviors. Lastly, we identify the requirements to investigate the complex relationship between the public and connected place managers, define all stakeholders clearly, and explore the patterns between specific connected place cybersecurity incidents and the methods used to transform public perceptions.